Non-Emergent Care Visits in a Turkish Tertiary Care Emergency Department after 2008 Health Policy Changes: Review and Analysis - Dundar, Cihad; Dal Yaylaoglu, Seydanur (BMC, 2022)
Background The Turkish government liberalized national healthcare policies in 2008 enabling Turkish citizens to seek general care in hospital emergency departments (ED). The number of ED visits has exceeded the total population every year for the last ten years. To explain this phenomenon and to identify trends and risk factors for non-emergent visits, we retrospectively reviewed the ED records of a tertiary hospital and the Turkish Ministry of Health bulletin. Methods This retrospective record-based study was conducted at a tertiary hospital in Samsun province of Turkey. A total of 87,528 records of adult patients who visited the ED between January 1 and December 31, 2017, were included in this study. We evaluated the pattern of ED use for non-emergent patients by age, gender, nationality, time of visit, means of arrival, ICD (International Classification of Diseases) diagnostic codes, triage codes, number of repeated and out-of-hours visits. We used the Turkish Ministry of Health statistics bulletins to compare the number of ED visits across the country by year. Results The non-emergent visit rate in ED was found 9.9%. The rate of non-emergent ED visits was significantly higher in the 18-44 age group, in the female gender, and in those who arrived at the ED without an ambulance. The number of non-emergent visits was very similar between weekends and weekdays but was significantly higher in working hours on weekdays than out-of-hours (p<0.001). The most frequent diagnostic code was "Pain, unspecified" (R52) and the rate of repeat visits was 14.8% of non-emergent ED visits. According to binary logistic analysis, non-emergency visits were associated with 18-44 age group (OR = 2.75), female gender (OR = 1.11) and non-ambulance transportation (OR = 9.86). Conclusions Our results showed that the 18-44 age group and female gender seek care in the ED for non-emergent problems more than the other parts of the population. The numbers of ED visits in the last decade continued to increase regardless of population growth. The health policy changes may have facilitated access to rapid physical and laboratory examination but also an exacerbation of the free-rider problem in ED services.
Dundar, Cihad/0000-0001-9658-2540;
Keywords: Abuse of Health Services; Crowding; Emergency Department; Government; Hospital; Integrated Care; Non-Emergent Visit; Policy; Triage; Turkey